2019
DOI: 10.3390/genes10050329
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Expression of Cytokines in a Theileria annulata-Infected Bovine B Cell Line

Abstract: This study aimed to establish a pure single-cell Theileria annulata-infected B cell line for the assessment of cytokine production in transformed and lipopolysaccharide (LPS)-stimulated cells. Several studies have aimed to identify cell surface markers in T. annulata-transformed cells; however, no information on cytokine production in these cells is available. To investigate the potential of the transformed cells to produce cytokines and their potential responses to antigen-stimulation, we purified mature B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…A transmission electron microscopic study, in which the effect of BPQ on oxidative phosphorylation in the mitochondria of E. multilocularis cells was measured in mice, revealed that treatment with BPQ prematurely disrupted parasitic mitochondria (Rufener et al, 2018). In studies to explore the survival pathways of infected cells (Guergnon et al, 2003), parasites exposed to the BPQ terminate their proliferation after the death of macroschizonts and trigger apoptosis of host cells within a few days (Rashid et al, 2019, Ram et al, 2021. A research conducted to compare the intestinal permeability of BPQ used for the treatment of Leishmania donovani infections with other drugs emphasized that the active substance that remained in the tissues for the longest time was BPQ (Venkatesh et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A transmission electron microscopic study, in which the effect of BPQ on oxidative phosphorylation in the mitochondria of E. multilocularis cells was measured in mice, revealed that treatment with BPQ prematurely disrupted parasitic mitochondria (Rufener et al, 2018). In studies to explore the survival pathways of infected cells (Guergnon et al, 2003), parasites exposed to the BPQ terminate their proliferation after the death of macroschizonts and trigger apoptosis of host cells within a few days (Rashid et al, 2019, Ram et al, 2021. A research conducted to compare the intestinal permeability of BPQ used for the treatment of Leishmania donovani infections with other drugs emphasized that the active substance that remained in the tissues for the longest time was BPQ (Venkatesh et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…T. annulata hijacks the host immune response to invade and transform leukocytes [37,38]. Knowledge of the pathogenic mechanisms that underlie tropical theileriosis is scanty but there is evidence that T. annulata schizont-infected cells causes failure of a protective immune response.…”
Section: Therapeutic Aspectmentioning
confidence: 99%
“…Tumor necrosis factor receptor (TNFR)-associated factor 6 (TRAF6) is a member of the TRAF family that can regulate signaling pathways by acting as an E3 ubiquitin ligase in addition to its role as an adaptor protein [3,4]. TRAF6 acts downstream of CD40 (a member of the TNFR superfamily) and the Toll-like receptor (TLR) superfamily to regulate the activation of the nuclear factor-kappaB (NF-κB) and mitogen-activated protein kinase (MAPK) signaling pathways [4][5][6][7], which enhances the activation of B cells and the expression of interleukin (IL)-6 [8], IL-4, IL-1 [9] and other downstream factors. Recently, TRAF6 expression was found to be upregulated in systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), hyperplastic thymuses and MG patient serum.…”
Section: Introductionmentioning
confidence: 99%